EVALUASI KEBERMANFAATAN KEBIJAKAN PEMBANGUNAN INFRASTRUKTUR JALAN TOL TRANS JAWA (CIPALI) BERDASARKAN TINJAUAN ASPEK EKONOMI DAN LINGKUNGAN - Hamidah, Riza (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
National development aims to improve people's welfare and encourage economic growth. Cipali toll road has become one of Java's main distribution routes for goods and public transportation. This policy paper proposes to provide an overview of the impact and benefits of the construction of the Cikopo-Palimanan toll road on economic and environmental aspects and to develop policy recommendations to overcome the issues/problems faced. The analysis approach carried out in this research is first, Statistical Trend Analysis and Spatial Trend Analysis of land use via the Google Earth platform with the hotspot analysis method. The results show that the Cipali Toll Road constructions can improve the economy of areas affected by development at a macro level with an average LPE above 5%. However, there were changes in land use in the period 2010-2022, which resulted in the area of rice fields decreasing from 1,001 hectares to 999 hectares. One of the expected policy recommendations is the synchronization of toll road construction policies with policies to increase national food crop production, through the development of toll road alternatives.